2012
DOI: 10.1002/eat.22025
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making and planning in full recovery of anorexia nervosa

Abstract: This study does not support results from other studies showing that rec AN participants perform better in decision-making. Results from this study show that planning is impaired even after full recovery from AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
2
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 59 publications
2
29
2
3
Order By: Relevance
“…However, the findings are discrepant with a number of studies that report recall and copy data from the Rey figure as a measure of central coherence [32]. Contrary to other findings, this study did not however, find any differences between recovered AN and the HC group [33]. The difference in effect size between currently ill ANs and recovered can be observed in Fig 2, with recovered ANs demonstrating a more global processing style than the AN group.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the findings are discrepant with a number of studies that report recall and copy data from the Rey figure as a measure of central coherence [32]. Contrary to other findings, this study did not however, find any differences between recovered AN and the HC group [33]. The difference in effect size between currently ill ANs and recovered can be observed in Fig 2, with recovered ANs demonstrating a more global processing style than the AN group.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, although brain volume in the AN patients increased, we did not have brain volume data on the healthy comparison group to evaluate whether these changes represented fully normalized volume in weight-restored AN patients. Other studies have found individuals recovered from AN to have similar or better IGT performance than comparison participants (Lindner et al, 2012; Tchanturia et al, 2007). Thus, it is possible that decision-making deficits observed in the current study would improve with longer duration of follow-up.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, poor decision-making in patients actively ill with AN may reflect a consequence of illness rather than a premorbid underlying impairment in decision-making that contributes to vulnerability. Researchers have evaluated decision-making in weight-restored patients with AN in order to disentangle state versus trait impairments; however, mixed findings have emerged from such studies (Bosanac et al, 2007; Danner et al, 2012; Lindner et al, 2012; Tchanturia et al, 2007). Studies have found poorer (Danner et al, 2012), similar (Bosanac et al, 2007; Tchanturia et al, 2007), and even superior performance (Lindner et al, 2012) in individuals recovered from AN compared to healthy comparison participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such decision-making deficits are often assessed using gambling tasks that require participants to learn from their mistakes and forgo immediate gratification in order to avoid longer-term negative consequences (Southgate et al, 2005). Although evidence is mixed (Guillaume et al, 2010; Lindner, Fichter, & Quadflieg, 2012), participants with EDs often display poorer outcomes compared to healthy controls, suggestive of deficits in global decision making and executive functioning (Boeka & Lokken, 2006; Danner et al, 2012). Further, preliminary evidence suggests that individuals with EDs may process food and illness-related cues (e.g., body image) differently, and fMRI studies reveal abnormal brain activation in cortical and subcortical regions of the brain associated with affective processing and planning of behavior (García-García et al, 2013; Southgate et al, 2005).…”
mentioning
confidence: 99%